Integrated marketing communication of Palm Resort in creating the public awareness / Yazariah Yazid - Yazid, Yazariah (Faculty of Business Management, 2001)
Palm Resort is a one of the resort hotel where its have the characteristics of a hotel, that called Sofitel and located with a three challenging golf course. It is known that Palm Resort provides form of accommodation and golfing to their customers. There are also some other supplementary services that would give the customer an enjoyable time, as PR objectives is to be the best golf and leisure resort in Malaysia and Asia. In order to be competitive every organization tries to implement their uniqueness and has more things to offer to the public. Researcher tries to see this the implementation of IMC by PR in promoting it product and services. Researcher tries to find out whether PR has utilized all the marketing communication tools in a way of t creating awareness to the public. From the findings researcher found that 32 percents of the non-customers of PR are not aware of PR existence. This due to lack of exposure and promotion tools used by PR in giving the publics information, and knowledge of PR. Besides that, subject choose may not be interested in finding the knowledge of PR. Researcher also found that the respondent is unaware of the integrated marketing communication. From the question, asked most of the respondents are unaware of the IMC in definition and implementation. At the last chapter, researcher has given conclusion of the findings and few suggestions that can be utilized by PR. This suggestion is given in form of the 7P's as theories in services marketing elements. Each element is clearly defined with few examples. Researcher also hopes that PR can review back their marketing strategies in order to be the leader in this market.